MicroRNA hsa-miR-29a-3p is a plasma biomarker for the differential diagnosis and monitoring of tuberculosis. (January 2019) - Ndzi, Elvis Ndukong; Nkenfou, Céline Nguefeu; Mekue, Linda Mouafo; Zentilin, Lorena; Tamgue, Ousman; Pefura, Eric Walter Yone; Kuiaté, Jules-Roger; Giacca, Mauro; Ndjolo, Alexis
Abstract: The diagnosis of tuberculosis (TB) continues to pose substantial public health problems. The quest for diagnostic biomarkers for TB is therefore primordial. This study aimed to evaluate the diagnostic and anti-TB treatment monitoring potentials of some selected miRNAs. Quantitative real time polymerase chain reaction and Receiver operating characteristics were used to estimate the ability of miRNAs to discriminate between healthy controls (HEC), latent (LTB) and active TB (ATB). The study showed that: hsa-miR-29a-3p, hsa-miR-155-5p and hsa-miR-361-5p were significantly upregulated in ATB compared to HEC while hsa-miR-29a-3p, and hsa-miR-361-5p were also significantly up-regulated in ATB compared to LTB (all P ≤ 0.05). MiR-29a-3p showed a good (81.37%) distinguishing performance in discriminating ATB from HEC and a good (84.35%) diagnostic performance in discriminating ATB from LTB. The performance of miR-29a-3p present in the blood in discriminating active TB from latent TB and healthy controls indicates it may be a useful biomarker for diagnosis of TB. Because this miRNA is found in blood (plasma) which is easy to collect compared to sputum it could be used in pediatric and extra-pulmonary TB cases.